**Concept: A basic skills on solving equations is tested here.**

**Solution: **

z+ (1−2z^2/z) = w/z

=> (z^2 + 1-2z^2 )/z = w/z

Cancel out the "w" in the denominators, add the terms in the numerator of the LHS and arrive at

1- z^2 = w

**(option c)**

Modified on: Tue, 12 Oct, 2021 at 1:32 PM

**Concept: A basic skills on solving equations is tested here.**

**Solution: **

z+ (1−2z^2/z) = w/z

=> (z^2 + 1-2z^2 )/z = w/z

Cancel out the "w" in the denominators, add the terms in the numerator of the LHS and arrive at

1- z^2 = w

Did you find it helpful? Yes No

Send feedbackSorry we couldn't be helpful. Help us improve this article with your feedback.

Help Desk Software
by Freshdesk Support Desk